Policymakers use A4NH evidence to inform decisions that guide and support nutrition-sensitive strategies in Bangladesh - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Policymakers in Bangladesh drew on evidence from the Transform Nutrition research program consortium (2011-2017), as well as an assessment of the National Nutrition Service (NNS), to inform the nutrition section of the National Five-Year plan in 2015. This plan is the framework for policy decisions made by the Government of Bangladesh. Since the National Nutrition Service assessment was completed, the Government of Bangladesh have implemented recommendations to strengthen frontline delivery through District Nutrition Officers, with support from UNICEF.